An Extended Taylor Model for Tidal Dynamics of the Korea Strait - Wu, Di; Fang , Guohong; Wei , Zexun; Cui , Xinmei (Current Advances in Geography, Environment and Earth Sciences Vol. 9, 2022)
The Korea Strait (KS), also called the Tsushima Strait, is a major navigation passage linking the Japan Sea (JS) to the East China Sea and Yellow Sea. There is a shortage of theoretical research because almost all existing studies of the tides in the KS used either data analysis or numerical modelling techniques. In this study, we construct a theoretical model, the extended Taylor model, for the tides in the KS-JS basin, which is idealized as four interconnected uniform-depth rectangular areas. The satellite altimeter and tide gauge observations, particularly for the locations of the amphidromic sites in the KS, are compatible with the model-produced K1 and M2 tides. The model's solution sheds light on the tidal dynamics in the following aspects. The tidal system in each area can be dissected into two oppositely travelling Kelvin waves and two families of Poincaré modes, with Kelvin waves dominating the tidal system. The incident Kelvin wave can be reflected at the connecting cross-section, where the water depth and basin breadth abruptly increase from the KS to the JS. The reflected wave exhibits a phase-lag increase relative to the incident wave of less than \(180^{°}\) at the connecting cross-section, generating amphidromic points in the KS. The aforementioned phase-lag increase depends on the wave's angular velocity and reduces as the wave's angular velocity decreases. The K1 amphidromic point is farther away from the connecting cross-section than the M2 amphidromic point, which is explained by this dependence.